The Kingfisher treasury of princess stories - "Waters, Fiona" (Kingfisher Publications: London, 2001)
Princesses conjure up an image of a glittering fairy-tale world to which children - especially little girls - are drawn. This is an anthology of a diverse collection of stories, from the sleeping beauties of traditional tales to the feisty heroines of modern fiction.
Keywords: Children's stories, English